2017
DOI: 10.1002/hbm.23819
|View full text |Cite
|
Sign up to set email alerts
|

5‐HTTLPR moderates the association between interdependence and brain responses to mortality threats

Abstract: While behavioral research suggests an association between cultural worldview and decreased anxiety of death, the underlying neurobiological mechanisms remain unclear. Using functional MRI, we investigated whether and how the serotonin transporter promoter polymorphism (5-HTTLPR), which has been associated with mental disorders such as anxiety and depression, moderates the associations between a cultural trait (i.e., interdependence) and self-report of death anxiety/depression and between interdependence and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 76 publications
0
9
0
1
Order By: Relevance
“…, 2010 ; Luo et al. , 2014 , 2017 ; Feng et al. , 2017 ).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…, 2010 ; Luo et al. , 2014 , 2017 ; Feng et al. , 2017 ).…”
Section: Discussionunclassified
“…mortality-unrelated negative affect, Luo et al. , 2014 , 2017 ). Our approach is sufficient to (i) provide a hyperscanning demonstration in the fields of MT and social interactions and (ii) inspire interventions aimed to potentially counteract maladaptive fears in humans ( Pan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Brain biochemistry is closely related to genetics as, for example, investigated with respect to risk for violence, as well as with the aim of finding medicines that can be used in medical treatment (see, e.g., [ 65 ]). To the best of the author’s knowledge, only serotonin has, thus far, been related to EA [ 22 ]. An overview of the subclasses in the class biochemistry is shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Individual characteristics moderate EA (I) [ 20 , 21 ]. In summary, a wide range of studies document that EA contributes to change in, for example, behavior (B), brain processing (B), and biochemistry (B) [ 3 , 22 ]. However, the existence of a physical link between EA and violent radicalization is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The dmPFC clusters in Ma et al’s study included both the prMFC and the arMFC and the ss/sl carriers showed stronger BOLD signal deactivation in both areas during reflection on negative traits of a friend. Moreover, Luo, Yu, and Han () found that the same region (dorsal anterior cingulate cortex [dACC]) showed stronger deactivation in response to death‐related words; however, such deactivation did not differ significantly between ss and ll allele carriers. When including cultural traits, such as interdependence, in regression analysis, Luo and colleagues found that in response to mortality threats, dACC/dmPFC activation showed a positive correlation with the interdependence trait in ss carriers but a negative correlation with interdependence trait in the ll carriers.…”
Section: Discussionmentioning
confidence: 99%